Abjection and Taboo Objects in Edward Bond’s Plays - Salma Khatoon (NUML Journal of Critical Inquiry)
What is most striking about Edward Bond’s plays is his unconventional representation of visible forms of violence and insanity. His plays deeply probe political, economic, and societal norms and values in provocative and thought-provoking ways for which he has often been compared to such contemporary British playwrights as Pinter, Brenton, Osborne, and Arden who profusely use violence and cruelty in their works. This article draws on Julia Kristeva’s theory of abjection and develops the argument that violence in Edward Bond can be placed within the field of abjection as its diverse manifestations appear as taboo objects, abject emaciated, festering bodies and sites of abjection that populate his dramatic world.